2009
DOI: 10.1002/geot.200900012
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the abrasiveness of soil and rock

Abstract: The abrasiveness of soil and rock is a determining factor for tool wear in all processes of rock excavation above and below ground, for example drilling, cutting and excavating. Although this is highly cost-relevant, no classification scheme has yet been produced, with which soil and rock can be classified according to their abrasiveness and wearing effect. Comparative investigations using three methods of determining abrasiveness were used to produce a proposal for the classification of rock material. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 4 publications
0
16
0
4
Order By: Relevance
“…Correlation between the two alternative testing methods is strong (R 2 = 0.77), especially if one takes into account the comparably small number of tests per rock type and the high variability of rock types. The correlation coefficient is hardly lower than comparable values from extensive test series given in literature [20]. Rock types like granulites and granites yield the highest values, while the lowest values are achieved again by dolomite and dunite.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Correlation between the two alternative testing methods is strong (R 2 = 0.77), especially if one takes into account the comparably small number of tests per rock type and the high variability of rock types. The correlation coefficient is hardly lower than comparable values from extensive test series given in literature [20]. Rock types like granulites and granites yield the highest values, while the lowest values are achieved again by dolomite and dunite.…”
Section: Resultsmentioning
confidence: 44%
“…The equivalent quartz content EQu [%] [17,18] according to [19,20], was estimated by using the mineralogical composition derived from x-ray analysis, where A i resembles the share of each mineral.…”
Section: Deval-testmentioning
confidence: 99%
“…where CAI = Cerchar index for natural surface CAI s = Cerchar index for smooth (saw-cut) surface Some researchers performed their tests on rough surfaces (Al-Ameen and Waller, 1994;Plinninger et al, 2003Plinninger et al, , 2004Rostami et al, 2005;Bakar, 2006;Thuro and Kasling, 2009;Gharahbagh et al, 2011;Duru, 2014) while others used sawn surfaces (Suana and Peters, 1982;West, 1989;Alber, 2008;Yaralı et al, 2008;Stanford and Hagan, 2009;Ghasemi, 2010;Rostami et al, 2014;Yaralı et al, 2013b;Duru, 2014). Al-Ameen and Waller (1994) mentioned that the surface finish had a minor effect on the results.…”
Section: Horizontal View Vertical Viewmentioning
confidence: 98%
“…Many researchers investigated the effect of various factors on the CAI which are petrographic properties from thin section analyses (such as grain size, mineralogical composition, degree of cementation, quartz content, the equivalent quartz content, matrix properties), physical and geomechanical properties of rocks (such as P-wave velocity, porosity, density, strength, and young modulus) (Suana and Peters, 1982;Al-Ameen and Waller, 1994;West, 1986;Deketh, 1995;Plinninger et al, 2003;Mathier and Gisiger, 2003;Plinninger et al, 2004;Yaralı, 2005;Yaralı et al, 2008;Lassnig et al, 2008;Thuro and Kasling, 2009;Oparin and Tanaino, 2009;Khandelwal and Ranjith, 2010;Deliormanlı, 2012;Rostami et al, 2014;Hamzaban et al, 2014). Alber (2008) demonstrated that the CAI was definitely stress-dependent.…”
Section: Introductionmentioning
confidence: 98%
“…The volcanic rock units (dykes) have CAI figures of up to 4.5. Based on the classification given by [12], the majority of rocks examined fall into the "abrasive" and "very abrasive" classes. Fresh andesite/diabase may be classified as "extremely abrasive".…”
Section: Physical and Mechanical Properties Of Rockmentioning
confidence: 99%